The Struggle For The Emergence of The Creative Industry Movement In Indonesia Through Citayam Fashion Week: What Mass Media Says - Asra Virgianita; Darynaufal Mulyaman; Gibraltar Andibya Muhammaad; Dewi Aulia Maharani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2026)
This article aims to map the mass media's framing of the CFW phenomenon, from its inception in mid-2022 to August 2023. This article uses a discourse analysis method, using news coverage data related to CFW. The CFW phenomenon has attracted attention from the general public, business people, social media influencers, and the government. This phenomenon began with young people who came from the buffer areas of Jakarta to the Sudirman district—the city center—to gather and wear identical and ‘eccentric’ clothes. The mass media play a vital role in constructing and framing CFW and disseminating it which brought more people every day. It also made many parties participate in commodifying CFW. In this regard, many people consider CFW to be synonymous with the Harajuku phenomenon, in terms of the fashion displayed and the role of the mass media. In addition, the emphasis on the element of 'creativity' in fashion used in CFW can be considered as a potential form of the government's creative economy policy, but it is not. This study found that the CFW's framing in mass media is dominated by three main discourses; (1) freedom of expression, (2) creative economy potential, and (3) class conflict and politicization.